Studies in transonic flow - Mohan, S. R. (Cranfield University, 1983)
This thesis is divided into, two distinct parts. Part I describes the design and development of an intermittent cryogenic wind-tunnel, in which the cold conditions are generated by the expansion of high pressure gas. The device uses a light piston moving in a tube and conditions during the running time are maintained constant by 'tuning' the piston motion, i. e. by Imatchingt the volumetric flow rate entering and leaving the tube. The results of the pilot tunnel (running time 0.3 secs. ) show that gas temperatures of about 110K can be obtained with a pressure ratio of 35. Part II describes the flow at, transonic speeds on five aerofoil sections (thickness-chord ratios 6 to 14%). The aerofoil sections were 6& 14% biconvex, an NACA 0012, a supercritical aerofoil CAST 7 and an 11.8% Joukowski profile. The tests were made in an intermittent$ perforated wall wind-tunnel which was developed from an existing supersonic wind-tunnel. A periodic flow due to shock-induced separation occurred over a narrow range of Mach numbers (from 0.82 to 0.90) on the 14% biconvex and 0012 sections at zero incidence, for both laminar and turbulent boundary layers. The frequency parameter(uc/Um) was about 1. Tests were also made with the aerofoils at incidence. Periodic flows occurred on the 14% biconvex, 0012 and 3oukowski profiles., The instability Mach numbers ranged from 0.84 to 0.90 and the frequency parameters from 0.40 to 1.36. A detailed study was made to determine the frequency spectrum of the tunnel noise and its influence on the periodic flow. Also, experiments were made to determine the influence of the aerofail geometry on the periodic flow. The experimental results on the 14% biconvex aerofoil have been compared with the numerical computations of the full Navier-Stokes equations performed at NASA, Ames.